Evaluation of In-Hospital and Community-Based Healthcare Utilization and Costs During the Coronavirus 2019 (COVID-19) Pandemic in Alberta, Canada: A Population-Based Descriptive Study - Kathy Liu; Elissa Rennert-May; Zuying Zhang; Adam G D’Souza; Alysha Crocker; Tyler Williamson; Reed Beall; Jenine Leal (Health Services Insights)
Background: Assessing the financial burden of COVID-19 is important for planning health services and resource allocation to inform future pandemic response. Objectives: This study examines the changing dynamics in healthcare utilization patterns and costs from a public healthcare perspective during the COVID-19 pandemic in Alberta, Canada. Design: Population-based descriptive study. Methods: All adult patients over the age of 18 years who had a laboratory-confirmed COVID-19 diagnosis in Alberta, Canada from March 1, 2020 to December 15, 2021. We described demographic information and community- and hospital-based healthcare utilization and costs. We compared changes in each outcome throughout the first four waves of the pandemic. Results: Among 255,037 patients, hospitalization incurred significantly higher costs ( N  = 20,603; aRR = 755.51; marginal cost: $21,738.17 CAD; P  < .01). Wave 2 recorded the highest cost for Emergency Department (ED) visits (aRR = 1.10; marginal cost: $79.19 CAD; P  < .01). Compared to Wave 1, Waves 2-4 all recorded significantly lower costs for out-patient visits. Wave 2’s in-patient cost for patients that required ICU admission was significantly lower than Wave 1 (aRR = 0.75; marginal cost: −$24,142.47 CAD; P  = .02). Conclusion: COVID-19 exerted a heavy toll on healthcare services, and the dynamics of this continue to evolve. Utilization of ED and in-patient services were particularly high. Severe infections requiring hospitalization and ICU admission are more expensive than non-hospitalized and non-ICU hospital admits. Future studies should clarify specific factors, such as sociodemographic determinants, that contribute to evolving patterns of health services consumption and changing trends in cost to holistically inform responses to future pandemics.